Emerging Carbon Nanotube Electronic Circuits, Modeling, and Performance. (17th February 2010) - Xu, Yao; Srivastava, Ashok; Sharma, Ashwani K.
Abstract : Current transport and dynamic models of carbon nanotube field-effect transistors are presented. A model of single-walled carbon nanotube as interconnect is also presented and extended in modeling of single-walled carbon nanotube bundles. These models are applied in studying the performances of circuits such as the complementary carbon nanotube inverter pair and carbon nanotube as interconnect. Cadence/Spectre simulations show that carbon nanotube field-effect transistor circuits can operate at upper GHz frequencies. Carbon nanotube interconnects give smaller delay than copper interconnects used in nanometer CMOS VLSI circuits.